Evaluation of kashar cheese meltability by tack and large amplitude oscillatory shear (LAOS) tests - Yildirim-Mavis, Cigdem; Ozmen, Duygu; Yakisik, Elif; Toker, Omer Said; Palabiyik, Ibrahim; Kaner, Ozlem (ELSEVIER SCI LTD, 2022)
Small amplitude oscillation shear (SAOS) analysis do not allow us to understand the viscoelasticity under large deformation related to eating experience such as cutting, spreading, or chewing. Large amplitude oscillation shear (LAOS) test was used to investigate the non-linear mechanical response of different kashar cheeses (pizza, toast, and fresh) in strain values ranging from 0.196 to 359%. Effect of strain and temperature on strain-stiffening and shear-thinning behaviours was revealed. Tack analysis revealed important information about the adhesive properties of kashar cheeses. According to the tack analysis results, temperature speeded up melting rates of cheese, thus the divergence of the probe was easier, and the required energy decreased. Up to now, no study has evaluated the meltability of kashar cheese together with the tack and LAOS tests. Tests used in the present study may ensure predictive knowledge to evaluate non-linear rheological properties and meltability of dairy products such as kashar cheese. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: RHEOLOGICAL PROPERTIES; MOZZARELLA CHEESE; LOW-FAT; NONLINEAR VISCOELASTICITY; SENSORY CHARACTERISTICS; CHEMICAL-COMPOSITION; CONDITIONS RELEVANT; CHEDDAR CHEESE; BEHAVIOR; MICROSTRUCTURE; Food Science & Technology